DENGAN METODE PEMBERIAN TUGAS DAPAT MENINGKATKAN HASIL BELAJAR SAINS MATERI JENIS HEWAN PADA SISWA KELAS IV SD NEGERI 011 TAMBUSAI KABUPATEN ROKAN HULU - Afrida Afrida (STKIP Rokania Pasir Pangaraian, 2019)
This study aims to improve the results of learning science in class IV 011 Tambusai Public Elementary School. This research was conducted at SDN 011 Tambusaiin class IV with a total of 26 students. The study was conducted in two cycles. in using the demonstration method students are directly involved in the learning process so that students become more creative and do not feel bored. By using the assignment method the learning process becomes more enthusiastic so as to produce satisfying grades. From that a teachers must be able to analyze and determine what kind of learning is suitable to be applied in the teaching class so that learning can take place well with perfect results. The results showed that an increase in student learning outcomes. Proved by the results of cycle 1 only 69.23% and in cycle 2 an increase to 88.46%